Metasurface-generating high purity narrow linewidth cylindrical vector beams: power scaling and its limitation - Li, Haokun; Xie, Lianghua; Zhang, Chun; Tao, Rumao; Shu, Qiang; Li, Min; Shen, Benjian; Feng, Xi; Xu, Lixin; Wang, Jianjun (Frontiers in Physics, 2023)
1.89 kW cylindrical vector beams (CVBs) at 1064 nm with the 3 dB linewidth being 21 GHz have been generated from a narrow linewidth all-fiber linearly-polarized laser by metasurface extra-cavity conversion. At the maximum output power, the transmission efficiency, mode purity of radially polarized cylindrical vector beams (RP-CVBs) are 97% and 92.7%, respectively. To the best of our knowledge, this is the highest power of narrow linewidth CVBs generated from fiber laser. The temperature of the metasurface is moderate, and the maximum temperature is 75.5oC at 1.89 kW, which means that the system can be further power scaled. The evolution of mode purity has been analyzed numerically, and the influence of high-order modes in laser source and thermal effects of metasurface has been calculated, which reveals that the presence of high-order modes and the temperature rise of metasurface degrade the mode purity of the CVBs.